Teacher and Students’ Perceptions of Quizizz Paper-Mode as English Formative Assessment Media on Tenth Grade Students - Putri, Lea Priscilla; Pujiawati, Nia (FKIP - Universitas Riau, 2025)
This study aims to find out the teacher and student’s perception of Quizizz paper-mode as English formative assessment media on tenth grade student at SMK PGRI 2 Karawang. The researcher uses Qualitative descriptive methods, to collect data using observation and interview as instruments. The population of this study was the tenth-grade students in the 2023/2024 academic year which consist of one teacher and six students. From the data distribution of observation and interview show that all participant has a positive perception. It can be concluded that teacher and students have positive perception of the use of Quizizz paper-mode. The teacher thought that the Quizizz paper-mode was a practical and beneficial media, and the students thought that the Quizziz paper-mode was fun and easy way to implement.